PERAN YAYASAN MUALAF CENTER INDONESIA DALAM MEMBINA KEAGAMAAN MUALAF DI DEPOK (Harmoni, 2020)
This paper is the result of field research obtained from the Mualaf Center Indonesia foundation. As one of the countries with the majority of the population being Muslim, Indonesia is a plural country that provides freedom of religion. Therefore the process of converting a person from one religion to another is an event that cannot be debated. However, religious conversion can cause new problems in the social order, including complaints of converts to changes in their lives, such as being isolated from the surrounding Muslim community, difficulty finding a place to study, and even being expelled from family members. This problem gave birth to many institutions or foundations that focus on fostering converts, one of which is the Depok branch of the Mualaf Center Foundation which is the place for research in this paper. By using qualitative methods that involve the role of researchers and informants in collecting data through observation, interviews, and documentation, this research results in the conclusion that 1. The Indonesian Center for Mualaf Foundation is generally quite successful as a foundation for converting converts 2. This guidance provides satisfaction for converts, such as fluency in reading the Koran and increasing insight into religious knowledge.
Keywords: Konversi Agama; Mualaf; Pembinaan Agama Pendahuluan